Estrategias lúcidas – Grupales “Judican” para incrementar el aprendizaje de las tablas de multiplicar en los alumnos del 3er grado de primaria de la I.E N° 00654, Lucila Portocarrero del distrito de Rioja - Garay Puelles, Abel Segundo (2011)
This researchin volved the application of Playful Strategies Group Sales "''JUDICAN" to increase the leve! of learning the multiplication tables in third grade srudents of Primary Education of School No. 00654 Lucila Portocarrero Rioja district. T:he investigation arase because in that educational institution, students are facing serious problems because they lack skills to salve simple multiplication exercises, which shows that the methodology is not adequate. In this sense, the overall objective of the research was to demonstrate that by applying Playful Strategies Gmup Sales "JUDICAN" students of third grade improve their leve! of learning in t€rms of multiplication, of course based on the history and existing theories, it was a:lso the research hypothesis. Regarding operations, we worked with a population sample, comprised of 12 boys and 8 girls, who were instructed in solving mathematical problems related to multiplication by JUDICAN Strategies. Regarding the assessment of learning, was the beginning and end of the research process through pretest and posttest. The research was conducted under a pre experimental design, with one group, fonnulating statistical hypothesis with a confidence leve! of 95%. For the testing of the hypothesis and according to the nature of the data was used to test the dlfference by paired Student t distribution, concluding that students who evidenced a !evel beginning at the end of the experiment showed a leve! of achievement mentioned in both dimensions assimilation, synthesis and application. Finally, we accepted the research hypothesis, which implies that the implementation of the Strategies Ludie Group Sales "JUDICAN" has significantly increased learning the multiplication tables in third grade students of Primary Education of School No. 00654 "Lucila Portocarrero".